Analysis of The Heavy Metal Content (Cd and Zn) in Water, Sediment, Roots, and Leafs of Sonnetaria sp. in Badung River Estuary Area - Gayatri, Ni Nyoman Puspa; Zulfa, Rozifatul; Parwayoni, Ni Made Susun; As-syakur, Abd. Rahman; Wijana, I Made Sara (Bumi Lestari, 2024)
The estuary area of the Tukad Badung river has the potential to experience heavy metal pollution because of its location for various domestic and industrial wastes also has dense shipping activities around it. This study aims to identify the heavy metal content of Cd and Zn in water, sediment, root, and leaf samples of Sonnetaria sp. that grows in the area. The results obtained from the analysis of the heavy metal content of Cd and Zn in water samples were 0.006 mg/L and 0.014 mg/L. The results of the analysis of heavy metal content of Cd and Zn in sediment samples were 0.406 mg/kg and 15.462 mg/kg, respectively. This shows that water and sediment samples are still below the applicable quality standards. The Bioaccumulation Factor (BCF) value shows that the roots and leaves of Sonnetaria sp. can accumulate heavy metal Cd by 0.034483 and 0.041872 and accumulate heavy metal Zn by 0.011059 and 0.016751. The calculation of Translocation Factor (TF) of Cd metal of 1.214286 and Zn of 1.51462 shows that Sonnetaria sp. belongs to the category of phytoextraction (TF>1). Based on the Igeo index, the estuary area of the Tukad Badung river is classified as unpolluted to moderately polluted by heavy metals Cd (Igeo: 0.436517) and not contaminated with Zn metals (Igeo: -2.76359).